STUDI POPULASI AYAM HUTAN MERAH (Gallus gallus) DI KAWASAN HUTAN DESA TUMBOHON KECAMATAN TALAWAAN MINAHASA UTARA - Glorio D. Pinaria; Fabiola B. Saroinsong; Hengki D. Walangitan; Saroyo - (COCOS, 2014)
ABSTRACTThis study aimed to estimate the population of red jungle fowl in the Tumbohon village. The method used in this study was a survey by the shaped line transect sampling to determine the population density (density) of red jungle fowl. It can be concluded that the density of the red jungle fowl in the forest area Tumbuhon village is 24.1 birds/km2. Value of density estimation based on the observation frequency in transects was 14.1 birds/km2 up to 34.1 birds/km2, while the value of density estimation based on the number of transects was 1.7 birds/km2 up to 46.5 birds/km2.Key words : Red Jungle Fowl, Tumbohon, Line Transect, Density